Exploring the Role of Shared Leisure Activities in Women's Marital Satisfaction - Abbasi Kharaju, Fatemeh; Toktas, Elif; Köse, Neşe (Psychology of Woman Journal, 2024)
Objective: This study aims to explore the role of shared leisure activities in women's marital satisfaction, providing insights into how these activities contribute to the quality of marital relationships.Methods and Materials: This qualitative study utilized semi-structured interviews to gather in-depth data from 25 married women. Participants were selected through purposive sampling to ensure a diverse range of experiences and backgrounds. The interviews focused on various aspects of shared leisure activities, including types, frequency, and perceived impact on marital satisfaction. Data were analyzed using NVivo software, following thematic analysis to identify key themes and patterns. Theoretical saturation was achieved after 20 interviews.Findings: The study identified five main themes related to the impact of shared leisure activities on marital satisfaction: emotional bonding, mutual support, relationship growth, conflict resolution, and the establishment of rituals and traditions. Participants reported that engaging in shared leisure activities significantly enhanced their emotional connection, provided mutual support, promoted personal and relational growth, facilitated effective conflict resolution, and helped establish meaningful rituals and traditions within their marriages.Conclusion: The findings underscore the critical role of shared leisure activities in promoting women's marital satisfaction. By engaging in activities that both partners enjoy and find meaningful, couples can strengthen their emotional connection, support each other, grow together, resolve conflicts more effectively, and create lasting traditions that enhance their relationship. The study highlights the importance of investing time and effort in shared leisure activities to improve the quality of marital relationships and overall well-being.